Exploring the Molecular Interactions of 7,8-Dihydroxyflavone and Its Derivatives with TrkB and VEGFR2 Proteins - Chitranshi, Nitin (Int J Mol Sci, 2015)
7,8-Dihydroxyflavone (7,8-DHF) is a TrkB receptor agonist, and treatment with this flavonoid derivative brings about an enhanced TrkB phosphorylation and promotes downstream cellular signalling. Flavonoids are also known to exert an inhibitory effect on the vascular endothelial growth factor receptor (VEGFR) family of tyrosine kinase receptors. VEGFR2 is one of the important receptors involved in the regulation of vasculogenesis and angiogenesis and has also been implicated to exhibit various neuroprotective roles. Its upregulation and uncontrolled activity is associated with a range of pathological conditions such as age-related macular degeneration and various proliferative disorders. In this study, we investigated molecular interactions of 7,8-DHF and its derivatives with both the TrkB receptor as well as VEGFR2. Using a combination of molecular docking and computational mapping tools involving molecular dynamics approaches we have elucidated additional residues and binding energies involved in 7,8-DHF interactions with the TrkB Ig2 domain and VEGFR2. Our investigations have revealed for the first time that 7,8-DHF has dual biochemical action and its treatment may have divergent effects on the TrkB via its extracellular Ig2 domain and on the VEGFR2 receptor through the intracellular kinase domain. Contrary to its agonistic effects on the TrkB receptor, 7,8-DHF was found to downregulate VEGFR2 phosphorylation both in 661W photoreceptor cells and in retinal tissue.